2019
DOI: 10.1128/iai.00851-18
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm-Derived Metabolites Suppress Pathology in a Mouse Model of Colitis and Inhibit Secretion of Key Inflammatory Cytokines in Primary Human Leukocytes

Abstract: Iatrogenic hookworm therapy shows promise for treating disorders that result from a dysregulated immune system, including inflammatory bowel disease (IBD). Using a murine model of trinitrobenzenesulfonic acid-induced colitis and human peripheral blood mononuclear cells, we demonstrated that low-molecularweight metabolites derived from both somatic extracts (LMWM-SE) and excretorysecretory products (LMWM-ESP) of the hookworm, Ancylostoma caninum, display anti-inflammatory properties. Administration to mice of L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 76 publications
0
48
0
Order By: Relevance
“…This suggests that other diagnostic techniques should be considered, especially those that use more reliably measured chemical markers. Studies on other parasitic nematode ESPs have revealed the presence of diagnostically unique nucleic acids, glycans, lipids, and non-proteinaceous small biomolecules [25,55,56]. Therefore, characterising the metabolome of T. canis ESPs and identifying specific metabolites would be valuable for developing more sensitive diagnostics and biomarkers of infection, as well as potential therapeutics that exploit the immunoregulatory properties of helminth ESPs [57,58].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that other diagnostic techniques should be considered, especially those that use more reliably measured chemical markers. Studies on other parasitic nematode ESPs have revealed the presence of diagnostically unique nucleic acids, glycans, lipids, and non-proteinaceous small biomolecules [25,55,56]. Therefore, characterising the metabolome of T. canis ESPs and identifying specific metabolites would be valuable for developing more sensitive diagnostics and biomarkers of infection, as well as potential therapeutics that exploit the immunoregulatory properties of helminth ESPs [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Sample derivatisation was performed as reported earlier for the GC-MS metabolomic analysis of ESPs derived from hookworms, whipworms and tapeworms [1,24,25]. The upper aqueous phase composed of 3:1 methanol:water (~900 µL) was aliquoted (50 µL) into a pulled point insert, dried using an evaporator at 30 • C (Christ RVC 2-33 CD, John Morris Scientific Australia) and then anhydrous methanol was added (50 µL).…”
Section: Targeted Analysis Of Polar Metabolites Using Gc-msmentioning
confidence: 99%
See 3 more Smart Citations